Heat transfer and Electric field Impacts on Ferrofluid Flow Over a Wedge - Loganayagi, V.; Kameswaran, Peri K. (Discontinuity, Nonlinearity, and Complexity, 2026)
The interest behind this article is to examine the electrohydrodynamic number, and heat transfer impacts on two dimensional, laminar, incompressible nanofluid boundary layer flow over a wedge. The well-known nanoparticle volume fraction model was applied to approximate the viscosity, thermal diffusivity, heat capacitance, and thermal conductivity of the nanofluid. The nanoparticles itemized here are Nickel, $Ni$, and Nickel Zinc Ferrite $Ni(Zn)O.Fe_2O_3$ with base liquid as water (Liquid $H_2O$). The governing system of equations is reduced in the system of nonlinear differential equations and solved numerically using MATLAB. The impact of the electrohydrodynamic parameter $k_1$, nanoparticle volume fraction $φ$, electric field functions $g_1$ on the velocity profile, the influence of the Prandtl number $Pr$, joule heating energy parameter $s_2$, and ion kinetic work parameter $s_3$ on temperature profile has examined. Further surface drag forces and the rate of heat transfer are inspected. A comparison is made with the available outcomes in the literature and present outcomes is a satisfactory concurrence with the findings in the literature for particular values. The velocity profile increases with an increase in electrohydrodynamic number, and also increases more in the case of Nickel than Nickel Zinc Ferrite. A decreasing trend in the velocity profile is observed for increasing values of electric field functions in both types of nanofluids. The temperature rises more in Nickel Zinc Ferrite than Nickel for an increase in the ion kinetic parameter. The cumulative effect of nanoparticle volume fraction and electric field function leads to decreases the heat transfer rate.